2016
DOI: 10.1016/j.jid.2016.05.127
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Exploits Epidermal Barrier Defects in Atopic Dermatitis to Trigger Cytokine Expression

Abstract: Patients with atopic dermatitis (AD) have an abnormal skin barrier and are frequently colonized by S. aureus. In this study we investigated if S. aureus penetrates the epidermal barrier of subjects with AD and sought to understand the mechanism and functional significance of this entry. S. aureus was observed to be more abundant in the dermis of lesional skin from AD patients. Bacterial entry past the epidermis was observed in cultured human skin equivalents and in mice, but found to be increased in the skin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
274
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 294 publications
(292 citation statements)
references
References 63 publications
10
274
0
8
Order By: Relevance
“…However, in mice where tissue stress is induced by contact hypersensitivity to DNFB, S. xylosus exacerbated the inflammatory response, assessed by increased recruitment of neutrophils and upregulated expression of IL-1β. These results are consistent with other studies showing that mice with barrier defects allow Staphylococcus to penetrate the epidermal barrier and subsequently increase cytokine expression in the skin (Nakatsuji et al, 2016). In some situations the cytokine production may be protective, such as during a fungal infection (Naik et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…However, in mice where tissue stress is induced by contact hypersensitivity to DNFB, S. xylosus exacerbated the inflammatory response, assessed by increased recruitment of neutrophils and upregulated expression of IL-1β. These results are consistent with other studies showing that mice with barrier defects allow Staphylococcus to penetrate the epidermal barrier and subsequently increase cytokine expression in the skin (Nakatsuji et al, 2016). In some situations the cytokine production may be protective, such as during a fungal infection (Naik et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Our whole tissue zymograms (Figure 3) demonstrated that the casein substrate was degraded at sites other than the epidermis. Since bacteria including S. aureus can penetrate the skin surface and elicit strong dermal immune responses (Nakatsuji et al , 2016; Nakatsuji et al , 2013; Zhang et al , 2015), it is possible these bacteria may also influence protease activity of dermal cells. It will be interesting to see if changes in skin protease activity are also dependent on skin barrier penetration by S. aureus .…”
Section: Discussionmentioning
confidence: 99%
“…The resulting increase in enzymatic activity leads to increased desquamation, altered antimicrobial peptide (AMP) and filaggrin (FLG) processing, and PAR-2 activation and inflammation (Borgono et al , 2007; Caubet et al , 2004; Sakabe et al , 2013; Stefansson et al , 2008). Increased protease activity may also play an important role in the communication of the microbiome with the skin immune system, and has recently been shown to directly influence epidermal cytokine production and inflammation by enhancing penetration of bacteria through the epidermis (Nakatsuji et al , 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Mice develop AD-like lesions when they are experimentally colonized by S.aureus (19, 20). However, in contrast to the exacerbation of disease and inflammation caused by S.aureus , other bacterial species found on normal skin appear to aid in normal immune homeostasis (21).…”
Section: Introductionmentioning
confidence: 99%